KEDEWASAAN MENIKAH PERSPEKTIF HUKUM ISLAM DAN HUKUM POSITIF DI INDONESIA - Azwandi Azwandi (Qiyas : Jurnal Hukum Islam dan Peradilan, 2018)
This study concludes  that: 1) maturity according  to Islamic law is marriage  done within the boundary of a person  has entered the baligh phase. Married adults are an attempt  to minimize the problems that make the concept  of sakinah,  mawaddah and rahmah households will not be achieved. Households need to be built on the basis of maturity so as to cause psychological maturity of each  partner  either husband or wife. This maturity will generate thoughts,  attitudes  and  behaviors that also mature in the household. Islamic Shari’a wants people  who want to marry is really people  who are ready mentally, physically and psy- chologically, mature  and  understand the meaning of a marriage  that is part of worship.  2) married  maturity  according  to Law No. 1 of 1974  is enacted in order  to provide  protection, justice and  safeguard the human side of Indonesian society. Married maturity  in Law No. 1 of 1974  aims to prevent  the occurrence of marriage  of children,  so that young  men  who become hus- band  and wife really have matured the soul of his body in forming a happy  and eternal family. According to the Compilation of Islamic Law, the age limit of an independent or adult child is twenty-one years, as long as the child is not physically or mentally disabled  or has never married